A monoclonal antibody targeting a large surface of the receptor binding motif shows pan-neutralizing SARS-CoV-2 activity - de Campos-Mata, Leire; Trinité, Benjamin; Modrego, Andrea; Tejedor Vaquero, Sonia; Pradenas, Edwards; Pons-Grífols, Anna; Rodrigo Melero, Natalia; Carlero, Diego; Marfil, Silvia; Santiago, César; Raïch-Regué, Dàlia; Bueno-Carrasco, María Teresa; et al. (Nature communications, 2024)
Here we report the characterization of 17T2, a SARS-CoV-2 pan-neutralizing human monoclonal antibody isolated from a COVID-19 convalescent individual infected during the first pandemic wave. 17T2 is a class 1 VH1-58/κ3-20 antibody, derived from a receptor binding domain (RBD)-specific IgA + memory B cell, with a broad neutralizing activity against former and new SARS-CoV-2 variants, including XBB.1.16 and BA.2.86 Omicron subvariants. Consistently, 17T2 demonstrates in vivo prophylactic and therapeutic activity against Omicron BA.1.1 infection in K18-hACE2 mice. Cryo-electron microscopy reconstruction shows that 17T2 binds the BA.1 spike with the RBD in “up” position and blocks the receptor binding motif, as other structurally similar antibodies do, including S2E12. Yet, unlike S2E12, 17T2 retains its neutralizing activity against all variants tested, probably due to a larger RBD contact area. These results highlight the impact of small structural antibody changes on neutralizing performance and identify 17T2 as a potential candidate for future clinical interventions. Characterisation of monoclonal antibodies against SARS-CoV-2 are useful for potential therapeutics or to understand more about the immune response to this virus. Here the authors characterise a monoclonal antibody that has a broad range of reactivity against SARS-CoV-2 variants and measure how it binds to its specific target region of the receptor binding domain.